DNA analyses of large pangolin scale seizures: Species identification validation and case studies - Ewart, Kyle M.; Lightson, Amanda L.; Sitam, Frankie T.; Rovie-Ryan, Jeffrine J.; Nguyen, Son G.; Morgan, Kelly I.; Luczon, Adrian; Anadon, Edwin Miguel S.; De Bruyn, Marli; Bourgeois, Stéphanie; Ouitavon, Kanita; Kotze, Antoinette; et al. (Elsevier B.V., 2021)
Pangolins are the mosttrafficked mammal in theworld, and all eightspecies are listed under CITESAppendix I.DNAbased wildlife forensic techniques are recognized as an important component of investigating a pangolin seizure. In particular, determining the species of pangolin in a seizure will 1) confirm the presence of pangolin to establish the legality of any trade, and 2) ensure appropriate laws are applied to theirfullest extentin a prosecution. Furthermore, valuable intelligence data, such as determining the geographic provenance of samples, can be produced through analysis of pangolin seizures. Despite the immense scale of the pangolin trade, standardized wildlife forensic techniquesfortesting pangolin seizures are in theirinfancy. To addressthis, here, we present a standardized genetic marker suitable for species identification of all eight pangolin species, and outline practical strategies for sampling large-volume pangolin scale seizures. We assessed the repeatability, reproducibility, robustness, sensitivity and phylogenetic resolution of this species identification test. Critically, the assay was tested in four wildlife forensic laboratories involved in testing pangolins. Additionally, we demonstrated the test’s utility to conduct geographic provenance analysis of Phataginus tricuspis samples. We analysed five large-volume pangolin scale seizures in Malaysia, which elucidated key targetspecies, poaching hotspots, and trafficking routes. Phataginustricuspis wasthe most commonly identified species(88.8%)from the seizure samples, and 84.3% of these P. tricuspisindividuals were likely sourced from western central Africa. We expect the imp